A Montfortian Education Charter Model for the 21st for Students in Schools in the Saint Gabriel's Foundation, Thailand - Mayod, Bro. Kriangsak; Mhunpiew, Nathara; Boonpram, Verayuth (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
This study aimed to develop and validate 'A Montfortian Education Charter Model (MEC) for the 21st Century for Students in Schools under the Saint Gabriel's Foundation, Thailand.' The researcher utilized both qualitative and quantitative methods to collect data for model development. Qualitative data were derived from document analysis of relevant literature revealing 47 desired characteristics essential for Montfortian students in the 21st Century. These characteristics were systematically categorized into ten dimensions. Quantitative data were collected by distributing a dual-response format questionnaire to a sample of 1904 students enrolled in grades 7-9 across 11 targeted schools under St. Gabriel Foundation, Thailand, during the first semester of 2023. The questionnaire demonstrated a validity index of 1.0 (IOC index) and a high reliability of 0.99 (Cronbach's Alpha Coefficient). The results from the PNImodified identified the need for improvement in developing the Model. The structure of the Model includes ten dimensions and the integration of student formation programs. A 30-hour training session involving 80 experimental students from grades 7-9 was conducted for the model assessment. The experiment indicated a statistically significant increase in the students' intended knowledge at a significance level of 0.01, confirming the efficiency and appropriateness of the Model. This research recommends that school leaders integrate MEC into the 21st-century educational framework at all levels of school administration with genuine commitment and patience. Furthermore, fostering the understanding and appreciation of MEC among school personnel through continuous education is essential for successful implementation. The findings of this study contribute valuable insights for educators and administrators seeking to enhance the educational experience of Montfortian students in the evolving landscape of the 21st Century.